A Proposed System for Push Messaging on Android - El Stohy, Rasha Abdel sattar; el Ghetany, Nashaat el Khamessy; el Gharib, Haitham Abdul Menem (International Journal of Interactive Mobile Technologies (iJIM), 2016)
Abstract— There is a remarkable growing interest in utilizing mobile communications to enhance the interactions between different partners in educational institutions, particularly in schools. However, how communicating with parents via applications while aren’t actively running is quite a challenging demand. On the other hand, the addressed success of the Android supporting features provided a good candidate to support applications with real time information. Moreover the Android platforms supports efficiently customizable notifications, which allow applications based on Google Cloud Messaging (GCM) to specify the pushed events. In this paper, we look at different push messaging alternatives available for Android. Push messaging provides an important aspect of server to device communication, and we specifically focus on the integration of cloud computing with mobile devices through the use of push-based technologies. The paper presents a proposed notification system; ToParent, that actively provide alerts and messaging between parents and schools. Also, we investigate the performance of two relevant push technologies for the Android devices .The proposed system was implemented using Eclipse. The system has been tested and validated. Evaluation have proven that the proposed ToParent enabled better efficiency, and good overall satisfaction of both parties; parents and school administrations.